Human Resource Development for Farmers and Extension Officers in Supporting Farming Business Management in Bone Regency - Syaripa Aeni; Sri Wahyuni; Andi Onasis; M. Awaluddin; Muhammad Luthfi Siraj (Jurnal Ad'ministrare, 2020)
District/city governments have a very important role in encouraging regional development. This study aims to examine strategies in the context of developing human resources for farmers and extension workers in supporting the management of rice farming in the Bone Selatan Regency. This study uses a quantitative approach with a unit of analysis of the combined farmer. The data collection techniques used in this study were questionnaires, observation, and interviews. The instruments used in this study were observation, questionnaires, and interviews. The data analysis used in this research is percentage analysis i. Education and training for farmers and extension workers must be provided regularly so that each farmer and extension worker is maintained for the competence of improving farming management.